Case report of a rare thumb exostosis - Ababneh, Faris A.; Essa, Monther M. A.; Qasaimeh, Motaz A.; Khub, Raed A.; Beidas, Mohamad J. (International Journal of Research in Medical Sciences, 2022)
Thumb exostosis is a rare, benign, and acquired bony tumor of the distal phalanx of the thumb, the mass itself is typically painless, but pressure on the nail plate can result in pain and deformity of the involved digit. This study was conducted at King Hussein Medical Centre in Amman, Jordan. A 38-year-old male patient, medically free, presented with a right thumb ulnar aspect hard mass, and pain at that site of his thumb. He started to notice it since 1 year. On examination, a hard bony lesion around 1×1 cm in size was present on the ulnar aspect of the right thumb tip, with tight but healthy skin over it. X-ray radiographs of the hand showed a bony lesion in continuity with thumb distal phalanx ulnar aspect native cortical bone. Excisional biopsy was done from dead ulnar approach without nail bed removal was done, and histopathology result confirmed the diagnosis of thumb exostosis and no recurrence occurred either on clinical or radiological follow up till date.